2009
DOI: 10.1104/pp.109.142976
|View full text |Cite
|
Sign up to set email alerts
|

In Folio Respiratory Fluxomics Revealed by 13C Isotopic Labeling and H/D Isotope Effects Highlight the Noncyclic Nature of the Tricarboxylic Acid “Cycle” in Illuminated Leaves  

Abstract: While the possible importance of the tricarboxylic acid (TCA) cycle reactions for leaf photosynthesis operation has been recognized, many uncertainties remain on whether TCA cycle biochemistry is similar in the light compared with the dark. It is widely accepted that leaf day respiration and the metabolic commitment to TCA decarboxylation are down-regulated in illuminated leaves. However, the metabolic basis (i.e. the limiting steps involved in such a down-regulation) is not well known. Here, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
187
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(203 citation statements)
references
References 51 publications
(41 reference statements)
14
187
0
Order By: Relevance
“…In agreement with this notion, it has been proposed that 2-oxoglutarate is synthesized in the light from a preexisting pool of citrate (Tcherkez et al, 2012a(Tcherkez et al, , 2012b. More generally, the slow labeling of organic acids and amino acids derived from them is consistent with the idea that glycolysis and the TCAC are inhibited in the light, when the TCAC operates in a noncyclic manner (Tcherkez et al, 2009(Tcherkez et al, , 2012aSweetlove et al, 2010). The very low enrichment in organic acids like isocitrate, fumarate, and malate can also be explained because the vast majority of these metabolites are located in the vacuole (Table 1; Beevers, 1966a, 1966b;Steer and Beevers, 1967).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In agreement with this notion, it has been proposed that 2-oxoglutarate is synthesized in the light from a preexisting pool of citrate (Tcherkez et al, 2012a(Tcherkez et al, , 2012b. More generally, the slow labeling of organic acids and amino acids derived from them is consistent with the idea that glycolysis and the TCAC are inhibited in the light, when the TCAC operates in a noncyclic manner (Tcherkez et al, 2009(Tcherkez et al, , 2012aSweetlove et al, 2010). The very low enrichment in organic acids like isocitrate, fumarate, and malate can also be explained because the vast majority of these metabolites are located in the vacuole (Table 1; Beevers, 1966a, 1966b;Steer and Beevers, 1967).…”
Section: Discussionsupporting
confidence: 64%
“…Organic acids involved in the TCAC, like isocitrate, 2-oxoglutarate, succinate, fumarate, and malate, were labeled relatively slowly, with only a small proportion being labeled at 60 min, as previously demonstrated (Tcherkez et al, 2005(Tcherkez et al, , 2009. As previously shown (Gauthier et al, 2010;Tcherkez et al, 2012a) the labeling of 2-oxoglutarate and Glu was also very slow.…”
Section: Labeling Of Amino Acids and Organic Acidssupporting
confidence: 52%
“…Inhibition of SDH will disrupt the tricarboxylic acid cycle, which leads to a noncyclic reaction pathway that has actually been described earlier to occur in plants and green algae in response to various conditions, including low oxygen availability (Vanlerberghe et al, 1989(Vanlerberghe et al, , 1991Hanning and Heldt, 1993;Schwender et al, 2006;Steuer et al, 2007;Boyle and Morgan, 2009;Tcherkez et al, 2009;Sweetlove et al, 2010;Grafahrend-Belau et al, 2013;Ma et al, 2014). Interestingly, similar observations were made on the relative levels of the metabolites associated with the tricarboxylic acid cycle in antisense SDH tomato (Solanum lycopersicum) plants, which were deficient in the expression of the iron-sulfur subunit of SDH .…”
Section: Hypoxia Leads To the Inhibition Of Sdh And Concomitantly Ofsupporting
confidence: 63%
“…The link between mitochondrial metabolism and photosynthetic performance described here is by no means without precedence and has received much attention in the form of both reverse genetic and inhibitor studies (Padmasree et al, 2002;Fernie et al, 2004b;Plaxton and Podesta, 2006;Sweetlove et al, 2007). Evidence has accumulated that the operation of respiration can boost photosynthetic performance (Nunes-Nesi et al, 2005;Plaxton and Podesta, 2006;Tcherkez et al, 2009); however, the fact that the effects observed here were mediated by a modification in stomatal performance drove us to focus on this parameter. Intriguingly, tomato plants with a deficiency in fumarase expression were previously shown to have a reduced flux through the TCA cycle, a large reduction in carbon dioxide assimilation, and restricted growth, due to impaired stomatal aperture (Nunes-Nesi et al, 2007b).…”
Section: Discussionmentioning
confidence: 94%